178 Gynaecological brachytherapy credentialing for radiation therapists: a quality improvement program. (18th September 2019) - Hanna, S; Lapuz, C; Lim, A
Abstract : Objectives: Gynaecological brachytherapy (GynBT) is an important part of gynaecological cancer management. At Olivia Newton-John Cancer Wellness & Research Centre (ONJCWRC), radiation therapists (RTs) are integral to the GynBT workflow. However, there is limited GynBT training available for RTs in Australia, resulting in inconsistent proficiencies. This is a preliminary report on the development and implementation of a credentialing program, providing a structured approach to GynBT training of RTs. Methods: A credentialing program was designed with modules and competency assessments to ensure efficiency and proficiency of RTs in the GynBT workflow. The program includes theoretical modules in anatomy, international GynBT guidelines, radiation safety and local protocols; and practical modules in equipment, ultrasound for GynBT, operating theatre procedures, MRI, contouring, applicator reconstruction, planning, quality assurance and treatment delivery. Learning strategies include self-directed learning, tutorials, practical sessions and third-party courses. The program concludes with an exit examination assessing major competencies. The expected time frame for the completion of the program is 12 weeks to 6 months. Results: The program was implemented in April 2018 with 2 RTs completing the program and passing the exit examination on first attempt. On post-program survey, the RTs felt the program was comprehensive, helping to build their confidence and proficiency in GynBT. Conclusions: A GynBT RT credentialing program was successfully developed and implemented to improve the quality of training at ONJCWRC. This program is mandatory for RTs joining the GynBT team. This program can provide a framework for implementation of GynBT training in other centres.